The Spatiotemporal Pattern of the Aerosol Optical Depth (AOD) on the Canopies of Various Forest Types in the Exurban National Park: A Case in Ningbo City, Eastern China - Yufeng Chi; Shudi Zuo; Yin Ren; Kaichao Chen (Advances in Meteorology)
The spatiotemporal distribution pattern of the aerosol optical depth (AOD) is influenced by many environmental factors, such as meteorological condition changes, atmospheric pollution, and topographic changes. Understanding the relationship between the vegetation land cover and the AOD would favor the improvement of forest ecosystem services. This quantitative research integrated remote sensing and ground survey data and used spatial statistical methods to explore the drivers that influence the AOD of the exurban national forest park and analyze the differences between various forest types. The driver analysis was carried out in the hot (Z ≥ 1.64) and cold (Z ≤ −1.64) spots of AOD in 2010 and 2017. Our results showed that (1) the forest type was proved to be the main factor contributing to the AOD pattern and (2) from 2010 to 2017, the average growth rate of broad-leaved forest, coniferous forest, bamboo, and shrub in hot spots was significantly higher than that in cold spots, while there was no significant difference in the mixed forest. The average growth rate of biomass densities of bamboo, coniferous forest, and mixed forest were higher than that of the shrub and broad-leaved forest. These findings provided the guidance for the rational allocation of tree species to increase the biomass and improve the ecosystem service values of forest parks.